Introduction of M40 target group is timely, say experts - The Sunday Post, (Kuching) (The Sunday Post, 2015)
KUALA LUMPUR: The introduction of the M40 target group in the 2016 Budget which addresses the rising cost of living faced by the middle income bracket is very timely, said experts.